Análise da atividade dos operadores industriais na fabricação de descartáveis - Gomes, Ruth Pereira (2020)
The present thesis has the general objective of analyzing the activity of machine operators in the manufacture of disposable trays and cups. Therefore, it was used the theoretical contributions of activity ergonomics and work psychodynamics to discuss the aspects that emerged in the research. Twenty workers from two industrial hubs in the industrial sector of a northeastern Brazilian state participated in this study. The machine operators answered a sociodemographic questionnaire and a semi-structured interview. For the analysis of the questionnaire data, a basic descriptive analysis was made and for the treatment of the interview materials we resorted to thematic content analysis. The results will be presented in three articles. The first article explores the discrepancy between prescribed and real work, focusing on the most recurrent variability, which demand expressive regulatory efforts from workers. The second article focuses on the risks present in the activity and their ways of coping. It addresses issues such as insertion and professional training, ways of coping with risks and security measures adopted with a view to mitigate them. The third article deals with the sources of pleasure and suffering at work and refers to the psychic relationship with work. Finally, it is hoped that this study can contribute to discussions that enable transformations in the workplace, especially in what was identified as harmful by the interviewees and that reinforces actions that promote the welfare of machine operators.